Explicating the Implicit: Working online, Focusing in person (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
Working online through the Covid epidemic lockdowns has shown many of us that embodied practice is not only possible online, but welcome. I explore how the therapist’s Focusing can offer an opportunity to be-with the client in embodied connection, regardless of physical or online emplacement, and particularly how felt sense can support us to approach ‘edgy’ material. I welcome comment and response, especially around the embodied possibilities in online work and from those with more Focusing experience than my own.
Keywords: Focusing; embodiment; intersectionality; liminality; bereavement